Successful management of ivermectin-induced blindness in an African lion (Panthera leo) by intravenous administration of a lipid emulsion. Issue 1 (December 2015) - Saqib, Muhammad; Abbas, Ghazanfar; Mughal, Mudassar
Abstract Background Ivermectin is widely used in veterinary practice for the treatment of ecto- and endo-parasites. In wildlife, an extra-label use this parasiticide is sometimes associated with toxicity. Different treatment regimens have been used in ivermectin toxicosis. The present report describes a successful reversal of ivermectin toxicity by intravenous administration of a commercially available lipid emulsion in a captive African lion (Panthera leo ). Case presentation A 2-year old captive African lion (Panthera leo) weighing 130 kg was presented with acute neurological impairment and bilateral blindness that had developed 24 h after ivermectin exposure. The animal was treated with a commercially available lipid emulsion along with supportive therapy and experienced complete recovery. Conclusion To our knowledge, this is the first case report of the use of lipid emulsion in the management of ivermectin induced blindness in an African lion and it appears that intravenous lipid emulsion may be an effective therapy in ivermectin toxicity in lions. Further testing in expanded clinical trials is clearly warranted.